Expediente e apresentação da edição: v. 14, n. 3, ago./dez. 2023 - Nez, Egeslaine de; Siebiger, Ralf Hermes (Eventos Pedagógicos, 2023)
Expediente e apresentação da edição - v. 14, n. 3, ago./dez. 2023.